The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-204x2012000600014
|View full text |Cite
|
Sign up to set email alerts
|

Selenato e selenito na produção e biofortificação agronômica com selênio em arroz

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da aplicação de doses de selenato e selenito na biofortificação de arroz (Oryza sativa) com Se, bem como a influência dessas formas de Se nos teores de P, S, Fe e Zn nos grãos. O experimento foi conduzido em casa de vegetação, em vasos com 4 dm 3 de um Latossolo Vermelho-Amarelo distrófico, de textura média, em arranjo fatorial 5x2, com cinco doses de Se (0, 0,75, 1,50, 3,0 e 6,0 mg dm -3 ) e duas formas de Se (selenato e selenito). Observou-se que o selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
2
10
0
3
Order By: Relevance
“…2B). This high efficiency regarding Se uptake and transportation by the xylem has been reported in several studies (Sharma et al, 2010; Ramos et al, 2011; Boldrin et al, 2012).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…2B). This high efficiency regarding Se uptake and transportation by the xylem has been reported in several studies (Sharma et al, 2010; Ramos et al, 2011; Boldrin et al, 2012).…”
Section: Resultssupporting
confidence: 79%
“…3D). The synergistic effect between selenate and sulfate has been previously reported (White et al, 2004;Ramos et al, 2011;Boldrin et al, 2012;Sousa et al, 2013). The evaluation of the nutrient content in the grains revealed significant (p £ 0.05) interaction between cultivars and Se only for the S content (Fig.…”
Section: Selenium Macro- and Micronutrient Content In Wheat Cultivarssupporting
confidence: 70%
“…Mycorrhizal plants could take up more metal nutrients via extraradical hyphae, which provide larger surface areas than the roots alone and reduce the distance for diffusion, thereby enhancing the absorption of immobile metal nutrients (Jakobsen et al, 1992). Previous studies without AMF inoculation found a decrease level of Micronutrients, when Se was applied in rice and forage grass (Boldrin et al, 2012;Ramos et al, 2012).…”
Section: Effect Of Se and Amf On Micronutrient Levelsmentioning
confidence: 99%
“…Additionally, in the case of the combined Zn and Se application, the BP associated with carbohydrate metabolism and lipid dynamics were also enriched. Such distinct GO profiles are likely related to the specific roles of Se and Zn in plant functioning as well as with specificities of Zn and Se biofortification processes, even considering a certain antagonism extent between these two minerals as regards their accumulation potential (Boldrin et al, 2012;Mangueze et al, 2018). This hypothesis is supported by the classification based on the MF, i.e., ion homeostasis in Se-biofortified flag leaves, probably related to the role of this mineral in controlling oxidative stress, the coenzyme/cofactor function of Zn in Zn-biofortified flag leaves, and a rather diverse set of GOs in the double biofortified flag leaves (Sunde, 2018).…”
Section: Discussionmentioning
confidence: 99%